Excitation and Inhibition Imbalance in Rett Syndrome - Li, Wei (Frontiers in Neuroscience, 2022)
A loss of the excitation/inhibition (E/I) balance in the neural circuit has emerged as a common neuropathological feature in many neurodevelopmental disorders. Rett syndrome (RTT), a prevalent autism spectrum disorder that affects 1:15,000 women globally, is caused by loss-of-function mutations in the Methyl-CpG-binding Protein-2 (Mecp2) gene. E/I imbalance is recognized as the leading cellular and synaptic hallmark that is fundamental to diverse RTT neurological symptoms, including stereotypic hand movements, impaired motor coordination, breathing irregularities, seizures, and learning/memory dysfunctions. E/I balance in RTT is not homogeneously altered but demonstrate brain region and cell type specificity instead. In this review, I elaborate on the current understanding of the loss of E/I balance in a range of brain areas at molecular and cellular levels. I further describe how the underlying cellular mechanisms contribute to the disturbance of the proper E/I ratio. Last, I discuss current pharmacologic innervations for RTT and their role in modifying the E/I balance.